Consolidación urbana, red de áreas verdes dentro del polígono urbano del cantón Santiago de Píllaro - Doménica Selene Paucar Tixicuro (2024)
This project focuses on the urban consolidation of the canton of Santiago de Píllaro through the implementation of a network of green areas, which addresses the lack of green public spaces and the prevalent urban sprawl, highlighting the importance of integrated planning to overcome urban segregation, promote regeneration and improve the quality of life of the population. To carry it out, the AEUB methodology is adopted, broken down into four contextually adapted stages, quantitative approaches are employed, and the parameters to be followed include the assessment of sustainability indicators, urban intervention strategies and the planning of a base plan to reverse identified deficiencies. The method applied is aligned with the quantitative paradigm, prioritizing practical solutions to reconfigure the urban structure and improve sustainability, while the approach is not limited to the description of challenges, but actively seeks concrete solutions, contributing to the understanding of urban consolidation and sustainable planning, based on quantifiable results obtained by sustainability indicators. Furthermore, this project aims not only to create green spaces, but also to revitalize underused or degraded urban areas, thus promoting greater social and economic cohesion in the canton. It seeks to encourage citizen participation in the identification of local needs and in making decisions related to the design and implementation of green areas, thus ensuring that the proposed solutions are relevant and beneficial for the community as a whole.